Heart failure with preserved ejection fraction (HFpEF): A missed diagnosis - Ahmed, Chaudury Meshkat (Bangladesh Journal of Medicine, 2023)
One of the most common cause for “unexplained shortness of breath” is heart failure with preserved ejection fraction (HFpEF), that is frequently missed by the physician. Untill the wide use of BNP/NT ProBNP the term even remained unfamaliar to many of them. More over the concepts that, to make a diagnosis of HFpEF, a diastolic dysfunction is mandatory accounts for another cause of missing the diagnosis of HFpEF.The reality is Half of the all forms of heart failure is attributed to HFpEF. The diagnosis based on : the symptom of heart failure, the raised BNP/NT Pro BNP and any of the two of the either left venticular hypertrophy (LVH)/ left atrial enlargement (LAE) or features of diastolic dysfunction( as assessed by an echocadiography).The first criteria that is the symptom of heart failure is often non specific and frequently difficult to distinguish from other clinical conditions. The levels of BNP/NT ProBNP also needed to be defined according to various clinical conditions where there may be raised level of this biomarkers in the absence of heart failure.On the other hand the echocardiographic detection of LVH, LAE or left ventricular diastolic dysfunction is either time consuming or inconclusive in many patients. The various clinical phenotypes of HFpEF in the clinical back ground also make it diffcult to “fit one size for all”. Our presentation will focus on the various facets of missed diagnosed HFpEF. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 181-182